Supervising Students During a Global Pandemic: Clinical Educators’ Perceptions of a Student-Led Telerehabilitation Service During COVID-19 - Megan H. Ross; Andrea Whitehead; Lauren Jeffery; Nicole Hartley; Trevor Russell (International Journal of Telerehabilitation)
Scope: In March 2020, COVID-19 restrictions prompted services delivered by student-led clinics in the university sector to transition to telehealth. This provided a unique opportunity to explore the challenges and opportunities faced by clinical educators when supervising students to deliver telehealth. Methodology: Semi-structured interviews were conducted with allied health clinical educators who supervised students on clinical placement who were required to provide services via telehealth. Clinical educators across the disciplines of audiology, occupational therapy, physiotherapy, and speech pathology were asked to reflect on their experiences and perceptions of the rapid transition to a telehealth model for student clinical placements. A content analysis approach was used to analyse qualitative data. Conclusions: From the perspective of clinical educators, student-led telehealth services can effectively meet client needs while achieving student learning outcomes. This study highlights many opportunities for student learning via telehealth in the clinical education environment and the role of the clinical educator in the learning experience.